2016
DOI: 10.1063/1.4967197
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid gating of ultra-thin YBa2Cu3O7−x films

Abstract: In this paper, we present a detailed investigation of the self-field transport properties of an ionic liquid gated ultra-thin YBa2Cu3O7−x (YBCO) film. From the high temperature dynamic of the resistivity (>220 K), different scenarios pertaining to the interaction between the liquid and the thin film are proposed. From the low temperature evolution of Jc and Tc, a comparison between the behavior of our system and the standard properties of YBCO is drawn.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 28 publications
(29 reference statements)
1
43
2
1
Order By: Relevance
“…This behavior has been reported before in the IL-gating of YBa 2 Cu 3 O 7−x films [12,24], where it was interpreted as an electric field driven slow redistribution process of the oxygen atoms in the copper oxide planes of the film [13,24]. …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This behavior has been reported before in the IL-gating of YBa 2 Cu 3 O 7−x films [12,24], where it was interpreted as an electric field driven slow redistribution process of the oxygen atoms in the copper oxide planes of the film [13,24]. …”
Section: Discussionsupporting
confidence: 74%
“…However, when applied to correlated oxide systems [5,10] there is substantial evidence that electrochemical processes related to interstitial oxygen is crucial in the gating process [11]. As for cuprate high temperature superconductors such as YBaCu 3 O 7−x , several reports suggested that the superconducting transition can be induced by (de)oxygenation of these materials by means of IL gating [12,13], while others suggested an electrostatic mechanism [14]. Dubuis et al [11] argued that the electric field of the electric double layer drives a redistribution of the oxygen atoms in the basal planes of the cuprate in an electrostatic fashion, while others have suggested an electrochemical process leading to oxygenation of the cuprate [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can not be simply attributed to the presence of grain boundaries, since the bulk conductivity is firmly in the disordered metal regime. However, the gate-induced AL is confined within few atomic layers [20,[39][40][41][42]] from a surface that features a much larger roughness 30 nm, and local "valleys" between the grains (up to ∼ 100 nm deep, see Fig.1a) may also lead to local percolative transport through the lighly-doped bulk. Therefore, disorder may be strongly amplified at the surface were the AL is confined, shifting the metallic edge of its MIT to much larger doping values with respect to the bulk.…”
mentioning
confidence: 99%
“…where ( ) = ; polar configuration (15) ( ) = √1 − 2 ; axial configuration (16) More details about the Jc(sf,T) analysis for p-wave symmetry can be found elsewhere [26,27]. This approach is recently applied for wide range of thin film unconventional superconductors [23,24,[26][27][28][29][30][31][32].…”
Section: Models Descriptionmentioning
confidence: 99%